Analisis Pelanggaran Peraturan Tarif Batas Atas PT. Wings Abadi Airlines Station Kualanamu Sumatera Utara - Salsabila, Indah; Yudianto, Kifni (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The large number of air transport enthusiasts has resulted in increasingly fierce competition between air transport business entities. In order to maintain fair competition, the government issued Minister of Transportation Regulation Number PM 20 of 2019 regarding procedures for calculating tariffs and Decree of the Minister of Transportation Number KM 106 of 2019 concerning upper limit tariffs. Currently there are fluctuations in avtur fuel which causes additional costs stipulated in the Decree of the Minister of Transportation Number KM 142 of 2022 concerning fuel surcharge. Even though there are regulations governing the determination of tariffs, there are still discrepancies in setting the rates sold. The purpose of this research is to find out what happened to the discrepancy, so that this can be adjusted immediately so that it does not harm either party. This study uses a qualitative method. Data collection techniques used by observation, interviews, and documentation. The informants used in this study were three Air Transport Inspectors at the Regional Airport Authority Office II. Data analysis techniques use the Miles and Huberman model, and to test the validity of the data use the triangulation method. The results of this study indicate that PT. Wings Abadi Airlines in setting fares is not adjusted to the Decree of the Minister of Transportation Number KM 142 of 2022. This is caused by rising fuel prices and insufficient passengers so they do not meet the operational costs incurred. This issue was followed up by reporting to the Directorate General of Civil Aviation and the Directorate General of Air Transportation. In addition, there is the imposition of administrative sanctions on PT. Wings Abadi Airlines. Keywords : Upper Limit Rates, Fuel Surcharge, PT. Wings Abadi Airlines, Airport Authority Office.